Controlling Drug Delivery Using Nanosheet-Embedded Electrospun Fibers for Efficient Tumor Treatment - Kumar S.; Singh A.P.; Senapati S.; Maiti P. (My University, 2025)
The objective of this study is to fabricate biodegradable polymers into scaffolds to embed drugs for tumor treatment without any toxic side effects. Scaffold preparation is optimized by changing the conditions, e.g., poly(lactic acid) concentration (10% w/v), applied potential (15 kV), flow rate (1 mL/h), distance between needle and collector (20 cm), and nanosheet concentration (4 wt % nanoclay), during electrospinning. A drug-embedded nanofiber scaffold is used to regulate the drug delivery in a sustainable manner utilizing the enhanced barrier effect from dispersed nanosheet and good interaction between the components. The effect of thermal treatment improves the stability and slower release of drug through alteration in microstructure. Cell culture studies using a nanofiber scaffold indicate its biocompatibility and applicability as a biomaterial for tumor treatment. Sustained drug release from the scaffold enhances the in vitro cancer cytotoxicity up to 85% in 3 days. In vivo studies clearly suggest suppression of tumor volume using scaffold as a patch over the tumor site as compared to control, pure drug, and drug-embedded film in the mice model. Evaluation of biochemical parameters indicates no toxic side effects for the liver and kidney using a hybrid scaffold as a delivery vehicle as opposed to severe liver injury in control and pure drug-treated mice group. Histopathology of the organs confirms the side effects for the pure drug-treated mice group against normal tissue morphology observed in scaffold-treated animals. Thus, sustained release of drug from this novel delivery vehicle has every potential to be used for tumor treatment more efficiently without any considerable side effects. Copyright © 2019 American Chemical Society.